2015
DOI: 10.1111/anae.13277
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of sugammadex vs neostigmine for reversal of neuromuscular blockade

Abstract: SummaryWe reviewed systematically sugammadex vs neostigmine for reversing neuromuscular blockade. We included 17 randomised controlled trials with 1553 participants. Sugammadex reduced all signs of residual postoperative paralysis, relative risk (95% CI) 0.46 (0.29-0.71), p = 0.0004 and minor respiratory events, relative risk (95% CI) 0.51 (0.32-0.80), p = 0.0034. There was no difference in critical respiratory events, relative risk (95% CI) 0.13 (0.02-1.06), p = 0.06. Sugammadex reduced drug-related side-effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(101 citation statements)
references
References 51 publications
3
88
1
4
Order By: Relevance
“…Abad-Gurumeta et al (11) reported that sugammadex reduced residual paralysis risk, respiratory adverse events, post-operative vomiting ratio according to neostigmine.…”
Section: Discussionmentioning
confidence: 99%
“…Abad-Gurumeta et al (11) reported that sugammadex reduced residual paralysis risk, respiratory adverse events, post-operative vomiting ratio according to neostigmine.…”
Section: Discussionmentioning
confidence: 99%
“…The main advantage of sugammadex compared to anticholinesterase inhibitors is its fast recovery time and its unique ability to reverse every level of NMB rapidly and effectively (55,67). This might be beneficial in situations, where deep neuromuscular blockade is required like in precision procedures, where unexspected movements might be deleterious (robot-guided procedures, neurosurgery, vocal cord and eye laser surgery) or in interventions where maximal muscle relaxation might improve operating conditions, like in laparscopic surgery (68).…”
Section: Debatementioning
confidence: 99%
“…This might be beneficial in situations, where deep neuromuscular blockade is required like in precision procedures, where unexspected movements might be deleterious (robot-guided procedures, neurosurgery, vocal cord and eye laser surgery) or in interventions where maximal muscle relaxation might improve operating conditions, like in laparscopic surgery (68). Meta-analysis identified fewer composite adverse events in using sugammadex compared to neostigmine (risk ratio [RR]: 0.6), with a number needed to treat (NNT) of 8 in order to prevent adverse events as follows (55,67): Bradycardia (RR: 0.16; NNT: 14), postoperative nausea and vomiting (RR: 0.52; NNT: 16), risk of overall signs of PORC (headlift-test, general muscle weakness, amblyopia, oxygen desaturation, POPCs) (RR: 0.40; NNT: 13) (55). Patients recieving sugammadex had 40% fewer adverse events compared to those who recieved neostigmine (55).…”
Section: Debatementioning
confidence: 99%
“…Neostigmine is associated with a higher risk of post operatory residual curaritazion (PORC), compared with sugammadex [23,24]. Sugammadex rapidly forms an essentially irreversible dose-dependent chelating complex with rocuronium and other aminosteroid muscle relaxants [25].…”
Section: Introductionmentioning
confidence: 99%